Catalytic combustions of two bamboo residues with sludge ash, CaO, and Fe2O3: Bioenergy, emission and ash deposition improvements. (10th October 2020) - Hu, Jinwen; Yan, Youping; Song, Yueyao; Liu, Jingyong; Evrendilek, Fatih; Buyukada, Musa
Abstract: The catalytic combustions of bamboo leaves (BL) and branches (BB) with textile dyeing sludge ash (SA), Fe2 O3, and CaO were qualitatively analyzed using thermogravimetric and Fourier transform infrared spectroscopy analyses, and thermodynamic equilibrium simulations. The catalysts (Fe2 O3  > SA > CaO) exerted a more pronounced effect in the char combustion (third) stage and enhanced the volatiles and comprehensive combustion indices with 40 °C/min. The catalysts (CaO > SA > Fe2 O3 ) reduced C- and N-containing gas emissions in the devolatilization (second) stage. CaO elevated the N-containing gas emission in the third stage, whereas Fe2 O3 and SA inhibited the formation of NO precursors. BB presented a higher risk of slagging than did BL, while the improved empirical indices of the ash deposition pointed to CaO as the optimal catalyst. Our simulations showed the final ash components of BL and BB were mainly as SiO2 and K2 Si4 O9 . The addition of CaO alone helped to form a high-melting point Ca-silicate. Although the addition of Fe2 O3 had no effect on the ash conversion, SA reduced the formation of K-silicate in the ash. The catalysts (CaO > SA > Fe2 O3 ) reduced the activation energy. Overall, the catalytic combustions improved the bioenergy and the N-containing gas emissions. SA as a Fe and Ca-rich industrial waste enhanced the combustion performance in terms of reductions in waste streams, gas emissions, and ash deposition. Our results supplied new insights into the efficient and clean bioenergy production of bamboo residues, and the waste utilization of SA. Graphical abstract: Image 1 Highlights: Two bamboo residues were combusted using sludge ash (SA), CaO and Fe2 O3 catalysts. Catalysts increased volatiles and combustion performances with a high heating rate. Catalytic emission reductions in NH3 and NO were CaO > SA > Fe2 O3 . The conversion of K–SiO2 was affected by CaO and SA but not by Fe2 O3 . CaO reduced the activation energy the most.